2017
DOI: 10.1186/s13033-017-0126-6
|View full text |Cite
|
Sign up to set email alerts
|

Medication challenges for patients with severe mental illness: experience and views of patients, caregivers and mental health care workers in Dar es Salaam, Tanzania

Abstract: BackgroundManagement of patients with mental disorders is inadequate in the majority of low and middle income countries. The main treatment modality for patients with severe mental disorders in these countries is mainly pharmacological approach. Patients face many challenges in meeting medication needs. In this context, high percentages of individuals who have severe mental disorders are not treated. Regular and adequate supplies of appropriate, safe and affordable medications are some of the important aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
(32 reference statements)
1
16
0
Order By: Relevance
“…Another study conducted in a Tanzanian psychiatric hospital reported that there was a lack of essential drugs for MHCUs. The unavailability of the essential psychotropic drugs was attributed to poor procurement practices and budget cuts because of competing demands, which delayed steady supply of the medication (Iseselo & Ambikile 2017 :16). Similar findings were reported in Ghanaian mental health institutions, where rampant corruption and bureaucracies delayed the constant supply of medication (Oppong et al 2016 :28).…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in a Tanzanian psychiatric hospital reported that there was a lack of essential drugs for MHCUs. The unavailability of the essential psychotropic drugs was attributed to poor procurement practices and budget cuts because of competing demands, which delayed steady supply of the medication (Iseselo & Ambikile 2017 :16). Similar findings were reported in Ghanaian mental health institutions, where rampant corruption and bureaucracies delayed the constant supply of medication (Oppong et al 2016 :28).…”
Section: Discussionmentioning
confidence: 99%
“…Past experience of treatment adverse effects, especially in medications and technology-based treatments, plays a deterrent role against utilization of MH services. Lack of adequate knowledge on necessity of continuous treatment and its possible adverse effects is a great challenge which dissuades patients from receiving care and decreases adherence to treatments (45,46). It is suggested that increasing patients' knowledge about different treatment choices and their potential side effects would be beneficial (23).…”
Section: Information System Was Introduced As a Key Building Block Ofmentioning
confidence: 99%
“…This problem is pertaining to the lack of information about various types of treatment and place of services(17,18,25,44,49).B-4-Treatment-related barriersB-4-1-Fear of treatment side effects: results of the study showed that patients' concern about side effects of available treatments has negative impact on utilization of MH services. Treatment side effects are mainly related to medications and technology-based interventions(18,23,45,46,48,49). B-4-2-Long-term nature of treatment: findings of the study indicated that long-term period of MH treatments is another barrier to the utilization of MH services.…”
mentioning
confidence: 99%
“…anti-psychotic medication, mood stabilisers). The implication of running out of these medications, for patients who rely on them to maintain psychiatric functioning is clear and has the potential to be a significant stressor for an individual (Iseselo and Ambikile, 2017). Similarly, for patients established on longterm analgesic agents or life sustaining medication used in chronic disease management it is likely that the pharmacy supply chain will remain a great stressor during any episode of isolation.…”
Section: Pharmacological Aspectsmentioning
confidence: 99%